Research on education in Quebec: between history and sociology - Hamel, Thérèse (Paidéia (Ribeirão Preto), 2000)
At the moment, when attention is called to the question of interdisciplinary, it can be observed that the relationships between Sociology and History have a particular evolution. They are independent disciplines and they are trying to influence one each other, bypassing their limits, although maintaining their specificity, with the objective of a better understanding of social phenomenon. Human Sciences are redefining their place in social area and it is important to think about the heuristic contribution of these two major sectors : History and Sociology.